2023
DOI: 10.3847/1538-4357/acbd48
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Benzene during Impacts in N2-dominated Atmospheres

Abstract: Benzene is a simple neutral aromatic compound found in molecular clouds, comets, and planetary atmospheres. It has been confirmed on Jupiter, Saturn, Titan, and is expected on exoplanets. In this paper, the decomposition of benzene in a simulated asteroid or comet impact into an N2-dominated atmosphere was investigated. The impact plasma was simulated with laser-induced dielectric breakdown and the gas phase decomposition products were observed using high-resolution Fourier transform infrared spectroscopy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…A high-resolution infrared Fourier-transform spectrometer (Bruker IFS 125HR, Bruker GmBH, Karlsruhe, Germany) is operated in the mid-infrared region between 600 cm −1 and 6000 cm −1 using a KBr beamsplitter and HgCdTe liquid-N 2 -cooled detector. The measured spectra are averaged over 10 scans [63,64]. The spectra are apodized with a Boxcar apodization function and analysed using the spectr library to obtain partial pressures of the detected components [65].…”
Section: Methodsmentioning
confidence: 99%
“…A high-resolution infrared Fourier-transform spectrometer (Bruker IFS 125HR, Bruker GmBH, Karlsruhe, Germany) is operated in the mid-infrared region between 600 cm −1 and 6000 cm −1 using a KBr beamsplitter and HgCdTe liquid-N 2 -cooled detector. The measured spectra are averaged over 10 scans [63,64]. The spectra are apodized with a Boxcar apodization function and analysed using the spectr library to obtain partial pressures of the detected components [65].…”
Section: Methodsmentioning
confidence: 99%
“…The measured spectra are averaged over 10 scans [58,59]. The spectra are apodized with a Boxcar apodization function and analysed using the spectr library to obtain partial pressures of the detected components [60].…”
Section: Methodsmentioning
confidence: 99%
“…Our experimental procedure combines closed, isochoric batch reactor with active gas flow, high-resolution Fourier transform infrared spectroscopy (FTIR) online detection, and analytical calibration-free data evaluation process. The experiments were performed on the ELISE experimental apparatus shown in Figure . This modular apparatus is designed for laser irradiation of samples with direct access to FTIR absorption and UV–vis emission spectroscopy for online analysis.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The parameter space of atmospheric compositions explored in this study provides a comprehensive framework for applying this chemistry to complex models of planetary atmospheres affected by impact shocks or other plasma events. In our previous research, HCN was identified as a common and significant product of the impact plasma reprocessing of planetary atmospheres. , This study centered on examining the stability of HCN in a nitrogen (N 2 ) bulk atmosphere, with variations in the initial partial pressures of HCN and H 2 O. The significant presence of N 2 aligns with dilution kinetics approaches, enhancing the experiment’s representativeness of planetary atmospheric conditions.…”
Section: Astrochemical Contextmentioning
confidence: 99%
See 1 more Smart Citation